An Innovative Approach to Airway Foreign Body Management in an Extremely Premature Neonate. (26th June 2019) - Hodge, Sarah E.; Kilpatrick, Lauren; Zdanski, Carlton
Abstract : This case report is a retrospective review of a challenging though ultimately successful removal of an airway foreign body in a 2‐day‐old premature female born at 23 weeks and 4 days gestation. A segment of a 5‐F surfactant catheter was cut and accidentally dislodged in the distal airway within the lumen of the patient's endotracheal tube. Ultimately, visualization was obtained using a 1.6‐mm KARL STORZ sialoendoscope, and retrieval was performed using sialoendoscopy forceps passed via the working channel of the sialoendoscope while maintaining ventilation. This case represents an innovative approach to complex airway foreign body management utilizing sialoendoscopy instruments. Laryngoscope, 130:1236–1238, 2020